2009
DOI: 10.1017/s0954394509990111
|View full text |Cite
|
Sign up to set email alerts
|

Cross-dialectal variation in propositional anaphora: Null objects and propositionalloin Mexican and Peninsular Spanish

Abstract: Despite the interest in null direct objects in Spanish, the case of direct objects with propositional antecedents, which complement cognition and communication verbs, remains mostly uninvestigated. This article investigates, from a comparative variationist perspective, null direct objects with propositional antecedents, variably coded by the clitic lo, in Mexican and Peninsular Spanish. Variable rule analysis of six Spanish corpora reveals a big difference between the two dialects in the frequency of overt vs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 35 publications
0
7
0
1
Order By: Relevance
“…3 Specifically, the analysis focused on verbs of communication and language like agradecer 'to thank', contar 'to count', decir 'to say', explicar 'to say', pedir 'to ask for' / 'to request' and preguntar 'to ask about'. Selection of these types was based on previous accounts by scholars, like Assela Reig Alamillo (2008Alamillo ( , 2009, who found that the null object was more likely to occur with verbs of communication and cognition. Limiting the contexts for analysis in this way allowed for a greater degree of comparability between different communities, since, individually, such verbs also show a high likelihood of use across all speakers and contexts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3 Specifically, the analysis focused on verbs of communication and language like agradecer 'to thank', contar 'to count', decir 'to say', explicar 'to say', pedir 'to ask for' / 'to request' and preguntar 'to ask about'. Selection of these types was based on previous accounts by scholars, like Assela Reig Alamillo (2008Alamillo ( , 2009, who found that the null object was more likely to occur with verbs of communication and cognition. Limiting the contexts for analysis in this way allowed for a greater degree of comparability between different communities, since, individually, such verbs also show a high likelihood of use across all speakers and contexts.…”
Section: Discussionmentioning
confidence: 99%
“…One thing that piques the interest with respect to null objects is that, in addition to being prevalent in situations of language contact, they have also been observed in areas that have no contact with other languages (Reig- Alamillo & Schwenter, 2007;Sainzmaza-Lecanda & Schwenter, 2017). For example, null objects occur in Mexico (Reig Alamillo, 2009;Schwenter, 2006). If it were the case that they were used widely, both socially and geographically, then their occurrence would seem to represent not so much a change due to contact, but rather a languageinternal tendency in Spanish, parallel to the situation of Brazilian Portuguese.…”
Section: Research Questions and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Women are the leaders of language change. This claim has been borne out through a number of studies spanning decades of socliolinguistic research on westernized societies (Eckert 1989, Eckert & McConnell-Ginet 2003, Labov 2001, Rissel 1989, Reig 2009, Shin 2013).…”
Section: )mentioning
confidence: 99%
“…Tokens were all coded for the sex (male or female) of the speaker. Women are often cited as the leaders of linguistic change (Eckert 1989, Eckert & McConnell-Ginet 2003, Labov 2001, Rissel 1989, Reig 2009, Shin 2013. If there is a change in progress with regards to the use of synthetic and periphrastic forms, we hypothesize, women may lead this change by favoring the periphrastic forms over synthetic forms when compared to men.…”
Section: Sexmentioning
confidence: 99%